Quasi-objects and actors in the web of belief. Formation of a national nuclear waste management system: the case of Finland - Kantola, Ismo; Silvan-Lempinen, Marianne (fi=Turun yliopisto|en=University of Turku|, 2010)
Paper presented in ISA RC23 meeting, Gothenburg July 16th 2010